An on-line microcomputer controlled static Var Compensator for power system laboratory experiments / Mad Azli Hambali - Hambali, Mad Azli (1993)
The objective of this project is the development of the laboratory model of an on-line individual control scheme of Static Var Compensator controlled by using microcomputer. The compensator circuit comprises of three wye connected capacitors together three airgap type linear inductors along with two anti-parallel thyristor in each arm connected in delta. An on line individual control scheme of the Static Var Compensator (SVC) which is constructed by thyristor controlled reactor (TCR) and fixed capacitor (FC) is designed to correct the power factor and balance the three phase load line current. The value of real power and reactive power (P-Q) measured at each sampling instant by the transducer between any two phases at the load bus terminal. Feedback signals from the line voltage and transducers sent to microprocessor through ADC0816 converter. A control circuit with simple hardware was designed to fire the thyristor whose delay angles were controlled by programmable interval timer 8253. The control circuit interface to the computer by using the prototype board data conversion circuit.